Regelungs- und Steuerungstechnik für Ingenieure. - Tröster, Fritz (De Gruyter Studium, 2015)
<!Doctype html public ""-//w3c//dtd html 4.0 transitional//en""> Volume 2 of this work covers the basic principles of feedback control systems. Illustrations and examples bring the teaching materials to life. Each unit begins by defining learning goals and formulating a core task to be completed by the end of the unit.